Common Variants Associated With OSMR Expression Contribute to Carotid Plaque Vulnerability, but Not to Cardiovascular Disease in Humans - van Keulen, Danielle; van Koeverden, Ian D.; Boltjes, Arjan; Princen, Hans M. G.; van Gool, Alain J.; de Borst, Gert J.; Asselbergs, Folkert W.; Tempel, Dennie; Pasterkamp, Gerard; van der Laan, Sander W. (Frontiers in Cardiovascular Medicine, 2021)
Background and Aims: Oncostatin M (OSM) signaling is implicated in atherosclerosis, however the mechanism remains unclear. We investigated the impact of common genetic variants in OSM and its receptors, OSMR and LIFR, on overall plaque vulnerability, plaque phenotype, intraplaque OSMR and LIFR expression, coronary artery calcification burden and cardiovascular disease susceptibility. Methods and Results: We queried Genotype-Tissue Expression data and found that rs13168867 (C allele) was associated with decreased OSMR expression and that rs10491509 (A allele) was associated with increased LIFR expression in arterial tissues. No variant was significantly associated with OSM expression. We associated these two variants with plaque characteristics from 1,443 genotyped carotid endarterectomy patients in the Athero-Express Biobank Study. After correction for multiple testing, rs13168867 was significantly associated with an increased overall plaque vulnerability (β = 0.118 ± s.e. = 0.040, p = 3.00 × 10−3, C allele). Looking at individual plaque characteristics, rs13168867 showed strongest associations with intraplaque fat (β = 0.248 ± s.e. = 0.088, p = 4.66 × 10−3, C allele) and collagen content (β = −0.259 ± s.e. = 0.095, p = 6.22 × 10−3, C allele), but these associations were not significant after correction for multiple testing. rs13168867 was not associated with intraplaque OSMR expression. Neither was intraplaque OSMR expression associated with plaque vulnerability and no known OSMR eQTLs were associated with coronary artery calcification burden, or cardiovascular disease susceptibility. No associations were found for rs10491509 in the LIFR locus. Conclusions: Our study suggests that rs1316887 in the OSMR locus is associated with increased plaque vulnerability, but not with coronary calcification or cardiovascular disease risk. It remains unclear through which precise biological mechanisms OSM signaling exerts its effects on plaque morphology. However, the OSM-OSMR/LIFR pathway is unlikely to be causally involved in lifetime cardiovascular disease susceptibility.